2016
DOI: 10.3892/ol.2016.4176
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic analysis of triple-negative breast cancer patients treated with adjuvant chemotherapy of fluorouracil, epirubicin and cyclophosphamide

Abstract: Abstract. The aim of the present study was to investigate the association between the clinicopathological and demographic factors, and the survival time of patients with triple-negative breast cancer (TNBC) in China. The patients had received adjuvant chemotherapy consisting of 5-fluorouracil, epirubicin and cyclophosphamide (FEC; 500 mg/m 2 cyclophosphamide, day 1; 75 mg/m 2 epirubicin, day 1; 500 mg/m 2 5-fluorouracil, days 1 and 8; every 3 weeks, for at least 4 cycles). The clinicopathological and demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…In the present study, the cumulative 5 years of DFS and OS of TNBC patients were 63.5% and 76.5%, respectively. This is in agreement with several other studies that observed a higher DFS and OS in TNBC patients [21,24,26,27]. Thus, it indicates that early-stage TNBC patients who underwent surgery and completed with cycles of TAC regimens had a higher DFS and OS.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the cumulative 5 years of DFS and OS of TNBC patients were 63.5% and 76.5%, respectively. This is in agreement with several other studies that observed a higher DFS and OS in TNBC patients [21,24,26,27]. Thus, it indicates that early-stage TNBC patients who underwent surgery and completed with cycles of TAC regimens had a higher DFS and OS.…”
Section: Discussionsupporting
confidence: 92%
“…Fluorouracil (5-FU) is used as a single palliative treatment in combination with other antineoplastic agents for the therapy of breast cancers 69 . According to National Comprehensive Cancer Network guidelines, 5-fluorouracil, epirubicin and cyclophosphamide (FEC) adjuvant chemotherapy regimen is the recommended regimen for breast cancer 70 . Classical CMF (cyclophosphamide, methotrexate and 5-fluorouracil) has shown good clinical efficacy for the treatment of TNBC 71 .…”
Section: Discussionmentioning
confidence: 99%
“…[76]. Although some therapeutic response is achieved through chemotherapy, patients with TNBC often relapse, thus associating this BC subtype with poor outcomes and shortened overall survival [7780]. Notably, TNBC, is more frequently diagnosed in women of African ancestry, and Kaiso’s role in TNBC racial disparity in incidence and outcomes will be discussed in a later section.…”
Section: A Jack Of All Trades: the Multifaceted Functions Of Kaiso Inmentioning
confidence: 99%